The Effect of HbA1C Variability and Lipid Profile on Carotid Intima-Media Thickness (cIMT) and Flow-mediated Dilatation (FMD) in children and adolescent with Type 1 Diabetes Mellitus at Saiful Anwar Hospital Malang - Ikeningrum, Dyah Ayu; Tjahjono, Cholid Tri; Kurnianingsih, Novi; Widito, Sasmojo; Putri, Valerina Yogibuana Swastika (Universitas Brawijaya, 2022)
BackgroundThere is a correlation between diabetes mellitus type 1 (T1DM) and a higher risk of heart disease. Atherosclerosis, which can be discovered early with cIMT (Carotid Intima-Media Thickness) and Flow Mediated Dilation (FMD) tests, contributes to the development of cardiovascular disease. HbA1c fluctuation and lipid profile can have an impact on cIMT and FMD.AimThe aim of this study is to determine the influence of HbA1c variability and lipid profile on cIMT and FMD levels in children T1DM patients treated at Dr Saiful Anwar Hospital Malang.MethodsThe study utilized a cross-sectional design and included 82 participants with Type 1 Diabetes Mellitus who were routinely treated at the Dr. Saiful Anwar Hospital Malang's pediatric outpatient clinic between January - July 2019 and December 2021 and-Â January 2022.ResultsThe correlation test revealed no significant connection between HDL (Ï=-0,029; p=0,796), LDL (Ï=-0.213; p=0.055), TG (Ï= -0.179; p= 0.107), and total cholesterol (Ï=-0.182; p= 0.101). Association tests revealed a positive correlation between LDL (Ï=0,318; p=0,004) and total cholesterol (Ï=0,230; p=0,038) levels and IMT. The correlation coefficient between HbA1C variability and FMD as evaluated by HVS was -0.498 (Ï=0.000; p=0.05), as was the correlation coefficient between HbA1c-SD (Ï=-0.467; p=0.000) and HbA1c-CV (Ï=-0.400; p=0.000). Additionally, a significant positive connection was discovered between IMT and the value of HbA1c variability utilizing HVS (Ï=0.455; p=0.000), HbA1c-SD (Ï=0.434; p=0.000), and HbA1c-CV (Ï=0.325; p=0.003). The linear regression analysis revealed that the three variables with the greatest influence on FMD were HVS (R=0.398), LDL (R=0.316), and HbA1c-SD (R=0.293). HVS (R=0.468), LDL (R=0.268), and total cholesterol (R=0.198) were the three most impactful variables on IMT. It is known that the combination of lipid profile and HbA1c fluctuation contributes 25.1% to FMD using this model. Meanwhile, the lipid profile and HbA1c variability together accounted for 34.5% of the variance in IMT.ConclusionVariability in HbA1c and lipid profile (LDL and total cholesterol) can contribute to an increase in intima-media thickness and a decrease in brachial artery FMD in children with T1DM.Â Â